21st Century Communications Could Change CCR Delivery. Issue 7 (1st July 2013) - Harris, Adrienne
Abstract : Since the first Consumer Confidence Report (CCR) was delivered in 1999, smart phones, social media, high‐speed broadband, and wireless connections have changed the way we communicate. Now those technologies are changing the way CCRs may be delivered.